Long-term Inflammation Transforms Intestinal Epithelial Cells of Colonic Organoids. (11th October 2016) - Hibiya, Shuji; Tsuchiya, Kiichiro; Hayashi, Ryohei; Fukushima, Keita; Horita, Nobukatsu; Watanabe, Sho; Shirasaki, Tomoaki; Nishimura, Ryu; Kimura, Natsuko; Nishimura, Tatsunori; Gotoh, Noriko; Oshima, Shigeru; et al.
Abstract: Background and Aims: Patients with ulcerative colitis [UC] are at an increased risk of developing colitis-associated cancer [CAC], suggesting that continuous inflammation in the colon promotes the transformation of colonic epithelial cells. However, the mechanisms underlying cell transformation in UC remain unknown. We therefore aimed to investigate the effect of long-term inflammation on intestinal epithelial cells [IECs] using organoid culture. Methods: IECs were isolated from mouse colon, and were cultured according to a method for a three-dimensional [3D] organoid culture. To mimic chronic inflammation, a mixture of cytokines and bacterial components were added to the medium for over a year. Cell signal intensity was assessed by 3D immunofluorescence. Cell transformation was assessed by microarray with gene set enrichment analysis. Results: Stimulation with cytokines resulted in a significant induction of target genes for the nuclear factor [NF]-κB pathway in colonic organoids. Following 60 weeks of continuous stimulation, cell differentiation was suppressed. Continuous stimulation also resulted in significant amplification of NF-κB signalling. Amplified NF-κB signalling by long-term stimulation remained in colonic organoids even 11 weeks after the removal of all cytokines. Some genes were specifically upregulated only in colonic organoids after the removal all cytokines following long-term stimulation. Conclusions: Colonic organoids stimulated with cytokines for a prolonged period were established as in vitro model to assess long-term epithelial responses to inflammatory cytokines. Chronic inflammation led to sustained NF-κB signalling activation in colonic organoids, resulting in cell transformation that might be related to the carcinogenesis of CAC in UC.